FORECASTING OF FERTILIZER INVENTORY IN UD. MENARA TANI WITH WEIGHTED MOVING AVERAGE (WMA) AND DOUBLE EXPONENTIAL SMOOTHING (DES) METHOD - Sinta Ramayani; Rizaldi; Muhammad Iqbal (Informatika, Universitas Jenderal Soedirman, 2022)
The process of supplying or stocking fertilizers at UD. Menara Tani is still carried out manually or only based on previous sales estimates, resulting in excess and shortage of fertilizer stocks. The purpose of this study was to determine the appropriate method in calculating the forecasting of ZA, Urea and KCL fertilizer supplies with a smaller error rate. The research method was conducted both Weighted Moving Average (WMA) and Double Exponential Smoothing (DES) with data collection conducted by observation and interview to owner of UD. Menara Tani. The results showed that the comparison of MAPE DES values ​​for each type of fertilizer was 24.70%, 21.59% and 20.12%. while the MAPE WMA values ​​are 4.53%, 39.51% and 38.90%. Forecasting applications with weighted moving average and double exponential smoothing can determined the prediction of fertilizer supplies in the next period. By comparing between WMA and DES, the best predictive value was found in the DES method.